CLIMATE VARIATIONS AND THE EARTHS ROTATION - Jochmann H.; Greiner-Mai H. (My University, 1996)
The similar temporal behaviour of climate parameters and the Earth's rotation leads to the assumption that there exists a relation between both phenomena. As is well known, the relationship between atmospheric dynamics and the Earth's rotation is proved to vary seasonally. In the area of decade fluctuations, which are more related to climate change, the 11- and 22-years periods could be proved to be generated by atmospheric dynamics. Longer periods are caused by core-mantle coupling torques which are possibly related to climate change via geomagnetic field variations.